Unraveling the Misconception About Deception and Nervous Behavior - Vrij, Aldert; Fisher, Ronald P. (Frontiers in Psychology, 2020)
In this article, we attempt to unravel the misconception about deception and nervous behaviour. First we will cite research demonstrating that observers believe lie tellers display more nervous behaviours than truth tellers; that observers pay attention to nervous behaviours when they attempt to detect deception; and that lie tellers actually feel more nervous than truth tellers. This is all in alignment with a lie detection approach based on spotting nervous behaviours. We then will argue that the next, vital, step is missing: Research has found that lie tellers generally do not display more than truth tellers the nervous behaviours laypersons and professionals appear to focus on. If observers pay attention to nervous behaviours but lie tellers do not come across as being nervous, lie detection performance is expected to be poor. Research has supported this claim. We finally discuss ideas for research into lie detection based on nonverbal behaviours.